Estudo da secagem de erva-mate (Ilex paraguariensis) - Pereira, Daniel Pilatti (2013)
The cultivation and industrialization of yerba mate (Ilex paraguariensis) have an important role in the economy of Paraná, since in most cases the plant is grown on family farming system, therefore producing thousands of jobs. Drying is one of the main processing stages of yerba mate and getting to know its variables will bring great benefits for both the processing companies and for the development of their equipment. Thus, the main motivation for developing this work, besides the direct interest on the part of the industry, was the absence of specific studies related to the drying of the species of mate grown in Brazil. This paper aims to obtain data modeling and experimental isotherms and drying kinetics of yerba mate.The equilibrium isotherms were obtained by the static method using saturated solution of sulfuric acid obtained at temperatures of 30°C, 45°C and 60°C and relative humidities in the range between 4.5 and 83%. Convective drying was performed using a fixed bed dryer for laboratory scale under different conditions of temperature: 55°C, 65°C and 75°C with air flow of 1.0 m/s, 1.5 m/s and 2.0 m/s. All experimental results were evaluated by using Maple software applied to the empirical equation that allowed the definition of the best model, which presented the highest coefficient determination (R²) and the lowest average deviation. It was concluded that the sorption isotherms of water mate in nature for the three temperatures analyzed were best fitted by the mathematical modified Halsey model. The kinetic curve for the drying temperature was 55°C better adjusted by the modified Newton model with three parameters adjusted. For temperatures of 65°C and 75°C, the modified Newton model with two adjusted parameters showed the best result. The results of this study are useful in the development of projects of industrial dryers, seeking greater savings and improved quality.